2014
DOI: 10.1186/2050-7771-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte and macrophage differentiation: circulation inflammatory monocyte as biomarker for inflammatory diseases

Abstract: Monocytes express various receptors, which monitor and sense environmental changes. Monocytes are highly plastic and heterogeneous, and change their functional phenotype in response to environmental stimulation. Evidence from murine and human studies has suggested that monocytosis can be an indicator of various inflammatory diseases. Monocytes can differentiate into inflammatory or anti-inflammatory subsets. Upon tissue damage or infection, monocytes are rapidly recruited to the tissue, where they can differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
772
1
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 838 publications
(818 citation statements)
references
References 62 publications
28
772
1
17
Order By: Relevance
“…The intermediate monocytes were associated previously with a proinflammatory role, being high producers of IL-1β and TNF in response to lipopolysaccharide (LPS), but low producers of reactive oxygen species (ROS), although showing high phagocytic ability [23]. It was suggested that intermediate monocytes are probably involved in antigen presentation and T cell activation [20]. An increase in the CD14…”
Section: Cd16mentioning
confidence: 99%
See 2 more Smart Citations
“…The intermediate monocytes were associated previously with a proinflammatory role, being high producers of IL-1β and TNF in response to lipopolysaccharide (LPS), but low producers of reactive oxygen species (ROS), although showing high phagocytic ability [23]. It was suggested that intermediate monocytes are probably involved in antigen presentation and T cell activation [20]. An increase in the CD14…”
Section: Cd16mentioning
confidence: 99%
“…S1). As described in the literature [20,21], we considered three monocyte subpopulations, one with high expression of CD14 and low or no expression of CD16 (CD14 (Fig. 2).…”
Section: + Peripheral Blood Monocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was suggested that PBM may be used after appropriate loading with contrast agents or other markers to visualize AS plaques non-invasively [40]. In early lesions the M2 phenotype predominates, whereas during AS development the frequency of M1 phenotype increases [38].…”
Section: The Biology Of Monocytes and Macrophagesmentioning
confidence: 99%
“…In response to inflammatory stimuli (i.e., LPS), the classical monocytes are selectively trafficked, in first instance, to the sites of inflammation, producing pro-inflammatory cytokines and contributing to local and systemic inflammation (Yang et al, 2014). These monocytes are highly infiltrative and can be differentiated into inflammatory macrophages, M1 acting in the acute phase of inflammation.…”
mentioning
confidence: 99%